Digitalisasi Bank Sampah Mandiri melalui Pendampingan Sistem Informasi Berbasis Web - Yulistia, Almi; Yahya; L M Samsu; Yupi Kuspandi Putra; Muh. Adrian Juniarta Hidayat; Fathurrahman (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
This community service program aims to support the digital transformation of Bank Sampah Mandiri Sandubaya by developing a web-based information system as an official, structured, and accessible platform for public communication. The partner previously relied solely on social media, which limited the organization’s ability to present information cohesively and maintain proper documentation. The implementation stages included needs assessment, system design, web development, content management training, and system evaluation. The results show that the developed website successfully integrates key information such as the organization’s profile, vision and mission, activity documentation, location map, and managed waste data. Furthermore, the training improved the staff’s ability to independently update and maintain website content. The web-based system has enhanced transparency, improved publication effectiveness, and strengthened the professionalism of Bank Sampah Mandiri in engaging with the community and potential stakeholders. Overall, this program provides an appropriate digital solution and supports the sustainability of environmental management efforts in Sandubaya.